Pathway analysis using 13C‐glycerol and other carbon tracers reveals a bipartite metabolism of Legionella pneumophila. Issue 2 (19th February 2016) - Häuslein, Ina; Manske, Christian; Goebel, Werner; Eisenreich, Wolfgang; Hilbi, Hubert
Summary: Amino acids represent the prime carbon and energy source for Legionella pneumophila, a facultative intracellular pathogen, which can cause a life‐threatening pneumonia termed Legionnaires' disease. Genome, transcriptome and proteome studies indicate that L. pneumophila also utilizes carbon substrates other than amino acids. We show here that glycerol promotes intracellular replication of L. pneumophila in amoeba or macrophages (but not extracellular growth) dependent on glycerol‐3‐phosphate dehydrogenase, GlpD. An L. pneumophila mutant strain lacking glpD was outcompeted by wild‐type bacteria upon co‐infection of amoeba, indicating an important role of glycerol during infection. Isotopologue profiling studies using 13 C‐labelled substrates were performed in a novel minimal defined medium, MDM, comprising essential amino acids, proline and phenylalanine. In MDM, L. pneumophila utilized 13 C‐labelled glycerol or glucose predominantly for gluconeogenesis and the pentose phosphate pathway, while the amino acid serine was used for energy generation via the citrate cycle. Similar results were obtained for L. pneumophila growing intracellularly in amoeba fed with 13 C‐labelled glycerol, glucose or serine. Collectively, these results reveal a bipartite metabolism of L. pneumophila, where glycerol and carbohydrates like glucose are mainly fed into anabolic processes, while serine serves as major energy supply. Abstract : The facultative intracellular bacterium Legionella pneumophila causes the severe pneumonia Legionnaires' disease. Extra‐ and intracellularly, L. pneumophila primarily metabolizes amino acids, but ‐ as we show here by using a new defined growth medium and a method termed isotopologue profiling ‐ also glycerol. The pathogen employs a bipartite metabolism, where glycerol and carbohydrates like glucose are mainly fed into energy‐consuming synthetic processes, while amino acids such as serine serve as major energy supply.